GAMBARAN DIATOMEA PADA PERAIRAN MUARA SUNGAI ROKAN KECAMATAN BANGKO DAN KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR SEBAGAI DIAGNOSIS PENUNJANG IDENTIFIKASI LOKASI KORBAN MATI TENGGELAM - Maliki, Muhammad; Afandi, Dedi; Kasry, Adnan (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diatomea investigation in the body of drowning victims is one of important investigation todetermination the drowning victims location. Diatomea is sould in the lung or another organfrom the body of victims as prove of drowning intra-vitality it means the victims are still alivewhen they are in the water and they are dead because of it. Diatomea species determining can beconcluded as a supporting diagnose to identify the location of drowning victims by comparingthe diatomea in the victims body with diatomea species in the water this research is a descriptiveresearch which is purposed for recognizing the species and the diatomea abundant in theRokan’s River Estuary of Bangko Sub-district and Batu Hampar Sub-district Rokan HilirRegency this research sample is taken from five research of stasions as purposive sampling. Thisresearch was done in April and May 2013 at Rokan’s River Estuary in Sub-district BangkoAnd Subdistrict Batu Hampar Rokan Hilir Regency. Diatomea investigation was done by usingBinocular microscope. This determining was done by using Masaharu and Yunfang atlas theabundant was searched by counted and numbered by using American Public Health Associations(APHA) formula.Diatomea was founded eight species they are: Aulocoseira sp, Diatoma sp, Nitzchia sp,Isthmia sp, Melosira sp, Navicula sp, Skeletonema sp, Bitdulphia sp. The abundant of diatomeais founded 11152,2 sel/L when the water comes up and I found 9132,6 sel/L when the water comedown with the Diatoma sp as the most dominant diatomea as a mount as 4986,4 sel/L when thewater comes up and with diatoma sp as the most dominant Diatomea as amount as 3799,8 sel/L.Keyword : Rokan’s river estuary drowning, species and abundant diatomea